Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Reconfigurable and real-time high-bandwidth Nyquist signal detection with low-bandwidth in silicon photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Meier, Janosch; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Optics Express)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain detection of a high-bandwidth Nyquist signal with a low-bandwidth silicon photonics Mach-Zehnder modulator based receiver. As the Nyquist signal has a rectangular bandwidth, it can be multiplexed in the wavelength domain without any guardband as a part of a Nyquist-WDM superchannel. These superchannels can be additionally multiplexed in space and polarization. Thus, the presented demonstration can open a new possibility for the detection of multidimensional parallel data signals with silicon photonics. No external pulse source is needed for the receiver, and frequency-time coherence is used to sample the incoming Nyquist signal with orthogonal sinc-shaped Nyquist pulse sequences. All parameters are completely tunable in the electrical domain. The feasibility of the scheme is demonstrated through a proof-of-concept experiment over the entire C-band (1530 nm–1560 nm), employing a 24 Gbaud Nyquist QPSK signal due to experimental constraints on the transmitter side electronics. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can process Nyquist signals of 90 GHz optical bandwidth, suggesting a possibility to detect symbol rates up to 90 GBd in an integrated Nyquist receiver.

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

Analysis of the effect of jitter and non-idealities on photonic digital-to-analog converters based on Nyquist pulses - Singh, Karanveer; Kress, Christian; Mandalawi, Younus; Misra, Arijit; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Emulation of integrated high-bandwidth photonic AWG using low-speed electronics - Singh, Karanveer; Meier, Janosch; Kress, Christian; Misra, Arijit; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Wideband SiN pulse interleaver for optically-enabled analog-to-digital conversion: a device-to-system analysis with cyclic equalization - Zazzi, Andrea; Müller, Juliana; Ghannam, Ibrahim; Battermann, Moritz; Rajeswari, Gayatri Vasudevan; Weizel, Maxim; Scheytt, J. Christoph; Witzens, Jeremy (Optics Express)
We present the design and experimental characterization of a silicon nitride pulse interleaver based on coupled resonator optical waveguide filters. In order to achieve a targeted free spectral range of 1.44 THz, which is large given the reduced optical confinement of the silicon nitride platform, individual ring resonators are designed with tapered waveguides. Its application to time-interleaved photonically-assisted ADCs is analyzed by combining experimental characterization of the photonic integrated circuit with a comprehensive model of the entire ADC. The impact of fundamental signal distortion and noise sources affecting the converter is investigated and suitable equalization techniques at the digital signal processing level are evaluated. The novel application of a simple but powerful equalization filter in the DSP domain allows for a significant improvement of the digitized signal SNR. An ENOB of 5 over a 75 GHz bandwidth (150 GS/s) and an ENOB of 4.3 over a 100 GHz bandwidth (200 GS/s) are expected to be achievable with compact and off-the-shelf single-section semiconductor mode locked lasers, that can be further improved with lower noise light sources.

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Light Scattering by Large Densely Packed Clusters of Particles - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Springer Series in Light Scattering - Volume 8: Light Polarization and Multiple Scattering in Turbid Media)
We review our results of numerical simulations of light scattering from different systems of densely packed irregular particles. We consider spherical clusters, thick layers and monolayers with realistic topologies and dimensions much larger than the wavelength of light. The maximum bulk packing density of clusters is 0.5. A numerically exact solution of the electromagnetic problem is obtained using the Discontinuous Galerkin Time Domain method and with application of high- performance computing. We show that high packing density causes light localization in such structures which makes an impact on the opposition phenomena: backscattering intensity surge and negative linear polarization feature. Diffuse multiple scattering is significantly reduced in the case of non-absorbing particles and near-field interaction results in a percolation-like light transport determined by the topology of the medium. With this the negative polarization feature caused by single scattering gets enhanced if compared to lower density samples. We also confirm coherent double scattering mechanism of negative polarization for light scattered from dense absorbing slabs. In this case convergent result for the scattering angle polarization dependency at backscattering can be obtained for a layer of just a few tens of particles if they are larger than the wavelength.
Keywords: tet_topic_scattering

Information extraction in photon-counting experiments - Schapeler, Timon; Bartley, Tim (Physical Review A)

Laser-lithographically written micron-wide superconducting nanowire single-photon detectors - Protte, Maximilian; Verma, Varun B; Höpker, Jan Philipp; Mirin, Richard P; Woo Nam, Sae; Bartley, Tim (Superconductor Science and Technology)
Abstract We demonstrate the fabrication of micron-wide tungsten silicide superconducting nanowire single-photon detectors on a silicon substrate using laser lithography. We show saturated internal detection efficiencies with wire widths ranging from 0.59 µ m to 1.43 µ m under illumination at 1550 nm. We demonstrate both straight wires, as well as meandered structures. Single-photon sensitivity is shown in devices up to 4 mm in length. Laser-lithographically written devices allow for fast and easy structuring of large areas while maintaining a saturated internal efficiency for wire widths around 1 µ m.
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Metals and Alloys; Condensed Matter Physics; Ceramics and Composites

Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Noise Processes and Nonlinear Mechanisms in Optoelectronic Phase-Locked Loop Using a Balanced Optical Microwave Phase Detector - Bahmanian, Meysam; Scheytt, J. Christoph (IEEE Transactions on Microwave Theory and Techniques)

Silicon Photonic Radar Receiver IC for mm-Wave Large Aperture MIMO Radar Using Optical Clock Distribution - Kruse, Stephan; Gudyriev, Sergiy; Kneuper, Pascal; Schwabe, Tobias; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph (IEEE Microwave and Wireless Components Letters)

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Two-Colour Spectrally Multimode Integrated SU(1,1) Interferometer - Ferreri, Alessandro; Sharapova, Polina R. (Symmetry)
Multimode integrated interferometers have great potential for both spectral engineering and metrological applications. However, the material dispersion of integrated platforms constitutes an obstacle that limits the performance and precision of such interferometers. At the same time, two-colour nonlinear interferometers present an important tool for metrological applications, when measurements in a certain frequency range are difficult. In this manuscript, we theoretically developed and investigated an integrated multimode two-colour SU(1,1) interferometer operating in a supersensitive mode. By ensuring the proper design of the integrated platform, we suppressed the dispersion, thereby significantly increasing the visibility of the interference pattern. The use of a continuous wave pump laser provided the symmetry between the spectral shapes of the signal and idler photons concerning half the pump frequency, despite different photon colours. We demonstrate that such an interferometer overcomes the classical phase sensitivity limit for wide parametric gain ranges, when up to 3×104 photons are generated.
Keywords: Physics and Astronomy (miscellaneous); General Mathematics; Chemistry (miscellaneous); Computer Science (miscellaneous)

Porous SiO2 coated dielectric metasurface with consistent performance independent of environmental conditions - Geromel, René; Weinberger, Christian; Brormann, Katja; Tiemann, Michael; Zentgraf, Thomas (Optical Materials Express)
With the rapid advances of functional dielectric metasurfaces and their integration on on-chip nanophotonic devices, the necessity of metasurfaces working in different environments, especially in biological applications, arose. However, the metasurfaces’ performance is tied to the unit cell’s efficiency and ultimately the surrounding environment it was designed for, thus reducing its applicability if exposed to altering refractive index media. Here, we report a method to increase a metasurface’s versatility by covering the high-index metasurface with a low index porous SiO2 film, protecting the metasurface from environmental changes while keeping the working efficiency unchanged. We show, that a covered metasurface retains its functionality even when exposed to fluidic environments.

Steady states of Λ-type three-level systems excited by quantum light with various photon statistics in lossy cavities - Rose, Hendrik; Tikhonova, O V; Meier, Torsten; Sharapova, Polina (New Journal of Physics)
Abstract The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high- Q cavities which strongly enhance the light–matter coupling. Cavities with low Q -factors are generally given less attention due to their high losses that quickly destroy quantum systems. However, bad cavities can be utilized for several applications, where lower Q -factors are required, e.g., to increase the spectral width of the cavity mode. In this work, we demonstrate that low- Q cavities can be beneficial for preparing specific electronic steady states when certain quantum states of light are applied. We investigate the interaction between quantum light with various statistics and matter represented by a Λ-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We show that cavity losses lead to non-trivial electronic steady states that can be controlled by the loss rate and the initial statistics of the quantum fields. We discuss the mechanism of the formation of such steady states on the basis of the equations of motion and present both analytical expressions and numerical simulations for such steady states.
Keywords: General Physics and Astronomy